SISI KEARIFAN LOKAL DALAM TERJEMAH AL-QUR`âN BERBAHASA BANJAR - Wardani Wardani (Khazanah: Jurnal Studi Islam dan Humaniora, 2020)
The local wisdom as perceived as particular knowledge is often contrasted to universal revealed knowledge of religion. This article is aimed at studying the local wisdom behind al-Qur`ân dan Terjemahnya Bahasa Banjar (the Qur`ân and Its Translation into Banjarese language), arguing that the two kinds of knowledge, either particular or universal, interact each other. Employing the ethics philosophy’s distinction between particular and universal, the discussion on the topic is focused on the description of local wisdom and the issues of particularity and universality, especially in relation to moral values embedded in cultural dimensions of the local language. The steps start from comparing Indonesian and Banjarese translation of some Qur`ânic vocabularies, then describing moral values in Banjarese culture in perceiving certain words, and finally searching for particular and universal dimensions of cultural ethics by comparing it with other ethics which is universally recognized. This article arrives at some conclusions. Firstly, the local wisdom is reflected in the forms of local moral values corresponding to the doctrines of the Qur`ân. Secondly, in relation to the idea of particularity and universality of moral values, the local wisdom behind this translation contains the two aspects, due to the fact that both dimensions constitute elements which interact with each other. The local values also underlay the use of local vocabularies. It means that the particular aspect of local wisdom transforms to universal one too. Besides, local wisdom does not only mean local knowledge but also means that it has a general affinity with other cultures.